Collective Action NGO dalam Pencegahan Korupsi Pengadaan Barang/Jasa Pemerintah di Sulawesi Selatan - Rifaid, Rifaid; Rusnaedy, Zaldi (Gorontalo Journal of Government and Political Studies, 2019)
This article discusses the collective action of NGOs in guarding and advocating corruption cases in South Sulawesi, specifically the procurement of Center Point of Indonesia (CPI) goods/services. The NGOs in the coalition are engaged in collective action in guarding the corruption of CPI, in which the group is focused on behalf of the Anti Corruption Community Coalition (KMAK) of Sulawei, incorporated from various NGOs namely ACC Sulawesi, PeRAK Institute, KOPEL Indonesia, FIK Non-Governmental Organizations and YASMIB Sulawesi. Media engagement is key to KMAK's success in guarding the CPI corruption, as an aggregation method to achieve its goals. The mass media coverage of reports, monitoring and discussions conducted by KMAK has made a number of formal state institutions take a look at the CPI case. The solid movement established by KMAK has transformed into a civil society movement that maintains a common goal of guarding the procurement of goods and services.  Artikel ini menjelaskan tentang collective action NGO dalam mengawal dan mengadvokasi kasus korupsi di Sulawesi Selatan, khususnya kasus pengaadaan barang/jasa Center Point of Indonesia (CPI). Dengan menggunakan metode penelitian kualitatif, penelitian ini menunjukan tindakan kolektif yang dilakukan NGO dalam mengawal dugaan korupsi CPI yaitu dengan cara berkoalisi, dan kelompok NGO tersebut mengatasnamakan Koalisi Masyarakat Anti Korupsi (KMAK) Sulawesi, yang tergabung dari berbagai NGO seperti (ACC Sulawesi, PeRAK Institute, KOPEL Indonesia, FIK Ornop Sulsel dan YASMIB Sulawesi) sebagai bentuk collective action. Keterlibatan media menjadi kunci keberhasilan KMAK Dalam mengawal kasus korupsi CPI, dan juga sebagai metode agregasi untuk mencapai tujuannya.